2020
DOI: 10.1101/2020.05.07.20094169
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Clinical, Radiological and Therapeutic Characteristics of Patients with COVID-19 in Saudi Arabia”

Abstract: BACKGROUND: Coronavirus disease 2019 (COVID-19) is a rapidly spreading global pandemic. The clinical characteristics of COVID-19 has been reported; however, there are limited researches that investigated the clinical characteristics of COVID-19 in the Middle East. The aim of this study is to investigate the clinical, radiological and therapeutic characteristics of patients diagnosed with COVID19 in Saudi Arabia. METHODS: This study is a retrospective single-centre case series study. We extracted data for pati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 28 publications
(29 reference statements)
0
27
1
Order By: Relevance
“…Additionally, there were 20.9% of patients without viral pneumonia symptoms [16], which was opposite to previous studies [69,70]. The asymptomatic cases varied from 21.9%-49.5% [66,68,93,94].…”
Section: Mortality and Fatalitycontrasting
confidence: 62%
“…Additionally, there were 20.9% of patients without viral pneumonia symptoms [16], which was opposite to previous studies [69,70]. The asymptomatic cases varied from 21.9%-49.5% [66,68,93,94].…”
Section: Mortality and Fatalitycontrasting
confidence: 62%
“…Additionally, there were 20.9% of patients without viral pneumonia symptoms [16], which was opposite to previous studies [69,70]. The asymptomatic cases varied from 21.9-49.5% [66,68,93,94].…”
Section: Clinical Spectrum Common Symptomsmentioning
confidence: 65%
“…In a report from the Middle East (Saudi Arabia)[39] that included 150 hospitalized adult patients (mean age 46.1 years), it was found that 28.8 and 26.0% of the COVID-19 population had hypertension and diabetes, respectively. The asthma prevalence was 2.7%, and 1 patient with asthma was admitted to the ICU.…”
Section: Methodsmentioning
confidence: 99%